NIZHNY NOVGOROD STATE UNIVERSITY OF ARCHITECTURE AND CIVIL ENGINEERING: 85 YEARS OF SUSTAINABLE DEVELOPMENT - Andrey A. Lapshin (Moscow Polytechnic University, 2016)
In 2015 Nizhny Novgorod state university of architecture and civil engineering (NNGASU) celebrates its 85th anniversary of the foundation. NNGASU is one of the leading architectural and engineering universities of Russia now, and it is a modern innovative educational complex. The article considers the history of NNGASU formation, analyzes the development of educational and research activities, international cooperation of NNGASU, reveals the role of the university in the training of highly qualified personnel.Keywords: Nizhny Novgorod state university of architecture and civil engineering,